A holistic framework for evaluating water security in agricultural systems in arid and semi-arid climatic regions - Shahla Dehghanpir; Ommolbanin Bazrafshan; Behnoush Farokhzadeh (Ain Shams Engineering Journal)
This study evaluates water sustainability in Iran’s cereal production systems (wheat, barley, and maize) from 2008 to 2021 by integrating the Water Footprint concept with multiple water scarcity indices (WSI, WPI, WDI, WSSI). The results demonstrate a critical dependence on blue water resources, accounting for 73.3 %, 70 %, and 80 % of total water requirements for wheat, barley, and maize production, respectively. Spatial analysis reveals striking regional disparities, with northern provinces like Guilan (WWSI = 0.01) experiencing low water stress, while arid central and eastern regions such as Yazd (WWSI = 0.95) and Markazi (MWSI = 1.90) face extreme water scarcity. The findings highlight how cereal cultivation, particularly water-intensive maize, exerts substantial pressure on Iran’s limited water resources. The proposed multi-index framework provides valuable insights for developing targeted water management strategies to enhance agricultural sustainability, optimize irrigation efficiency, and reduce reliance on unsustainable water sources in water-stressed regions, offering crucial guidance for policymakers in arid and semi-arid environments.